Combination of transbronchial cryobiopsy based clinic-radiologic-pathologic strategy and metagenomic next-generation sequencing for differential diagnosis of rapidly progressive diffuse parenchymal lung diseases - Sun, He; Chen, Rongzhang; Li, Tian; Gao, Jinli; Gu, Xia; Zhu, Xuyou; Jin, Lianfeng; Shi, Yi; Li, Qiang (Frontiers in Cellular and Infection Microbiology, 2023)
Background The complicated spectrum of rapidly progressive diffused parenchymal lung diseases (RP-DPLD) creates obstacles to the precise diagnosis and treatment. We evaluated the differential diagnostic value of transbronchial cryobiopsy (TBCB) based clinic-radiologic-pathologic (CRP) strategy combined with bronchoalveolar lavage fluid (BALF) metagenomic next-generation sequencing (mNGS) in RP-DPLD patients. Methods RP-DPLD patients who underwent the diagnostic strategy of TBCB-based CRP combined with BALF mNGS at Shanghai East Hospital from May 2020 to Oct 2022 were retrospectively analyzed. Clinical characteristics were summarized, including demographic data, high-resolution computed tomography (HRCT) findings, histopathology of TBCB and microbiological results. Diagnostic value of the combined strategy, as well as the sensitivity, specificity, and positive detection rates of mNGS were evaluated. Results A total of 115 RP-DPLD patients were enrolled, with a mean age of 64.4 years old and a male proportion of 54.8%. The pulmonary imaging findings in most patients were complex and diverse, with all patients showing bilateral lung diffuse lesions in HRCT, and progressively aggravated imaging changes within one month. After combining TBCB-based CRP strategy with mNGS, all participants received a corresponding diagnosis with 100% diagnostic yield. In these patients, 58.3% (67/115) were diagnosed with noninfectious RP-DPLD and 41.7% (48/115) with infection-related RP-DPLD. There were 86.1% of cases with known etiology according to the DPLD classification. BALF mNGS and traditional pathogen detection methods were performed in all patients, the positive detection rates were 50.4% (58/115) and 32.2% (37/115), respectively. Meanwhile, the mNGS showed significantly higher sensitivity and negative predictive value than the traditional pathogen detection methods for the diagnosis of infection-related RP-DPLD (100% vs 60.4% (p<0.001), 100% vs 75.6% (p<0.001), respectively). Among noninfectious RP-DPLD patients, the true negative rate of mNGS was 85.1% (57/67). All patients had their treatment regimen modified and the 30-day mortality was 7.0%. Conclusion The novel strategy of TBCB-based CRP combined with mNGS provided dependable and sufficient evidence for the diagnosis, meanwhile further improved the accuracy of RP-DPLD treatment, as well as the prognosis of patients. Our results highlight the significant value of combined strategy in determining whether the RP-DPLD patients were infection associated or not.